Basics of Akkadian : a grammar, workbook, and glossary - Hugenberger, Gordon Paul; Erickson, Nancy L. (Grand Rapids, MI. Zondervan Academic, 2022)
"Basics of Akkadian, by Gordon P. Hugenberger with Nancy L. Erickson, is a one-semester introductory textbook to the Akkadian language. It provides students with essential tools in order to quickly grasp the Akkadian language and move into translation"--
"Equips Students with Essential Tools to Quickly Grasp Akkadian and Move into TranslationBasics of Akkadian: A Complete Grammar, Workbook, and Lexicon, by Gordon P. Hugenberger with Nancy L. Erickson, is a one-semester introductory textbook to the Akkadian language. The grammar provides students with essential tools in order to quickly grasp the Akkadian language and move into translation. Designed around the Laws of Hammurabi, each chapter includes: Explanation of grammatical points, signs that need to be learned, and vocabulary exercise. Short contributions that highlight the unique significance of learning Akkadian for the studies of the Hebrew Bible are also included throughout the grammar. By the end of the grammar, students will have: Read through a sixth of the Laws of Hammurabi, learned how to read Neo-Assyrian script, transliterate that script, normalize the transcription, and translate. Robust appendices at the back of the book include major paradigms, a list of cuneiform signs, an alphabetical list of V, CV and VC cuneiform signs, and a complete Akkadian glossary. Basics of Akkadian is designed for classroom use as well as the independent learner. Students will acquire all the necessary tools to either pursue additional studies of the Akkadian language or to utilize the information gained for better understanding the cognitive environment of the biblical world and to engage thoughtfully and carefully with Akkadian literature"--
Includes bibliographical references (pages 341-344) and index.
Keywords: Akkadian language -- Grammar; Akkadian language; RELIGION / Biblical Reference / Language Study; RELIGION / Biblical Studies / History & Culture